Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles